Reconstruction of the thermally quenched glow-curve of Al2O3:C - Dallas, G. I.; Afouxenidis, D.; Stefanaki, E. C.; Tsagas, N. F.; Polymeris, G. S.; Tsirliganis, N. C.; Kitis, G. (Physica status solidi. A, Applications and materials science, 2008)
The experimental glow‐curve of Al2O3:C is highly disturbed due to the strong thermal quenching effect present in this material. Therefore, the real glow‐curve shape of this material is unknown. The present work describes an attempt to reconstruct the glow‐curve shape of Al2O3:C samples with different TL peak structures. The reconstruction procedure is performed in two steps. In the first step, the very narrow glow‐curves are fitted with the product of known kinetic equations and the expression giving the thermal quenching efficiency. From this procedure the quenching parameters are estimated. Next, the experimental glow curves are reconstructed (corrected for thermal quenching) dividing them by the quenching efficiency using the evaluated parameters from the first step. This step was applied to all types of glow curve structures. It was found that the quenching parameters estimated from the above procedure for Al2O3:C are in very good agreement with those reported in the literature. The results indicate that the method can be used as an alternative method for the evaluation of the quenching parameters and the reconstruction of the real (without quenching) glow‐curves of various materials. (© 2008 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)